1980
DOI: 10.1016/s0022-5347(17)55792-4
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Urinary Calculi Associated with Toluene Sniffing

Abstract: A young man who presented initially with a ureteral stone was found to have toluene-induced renal tubular acidosis. Persistent toluene sniffing resulted in recurrent calculi and life-threatening hypokalemic paralysis. The pathophysiology, classification and treatment of renal tubular acidosis are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

1982
1982
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(8 citation statements)
references
References 6 publications
0
6
0
2
Order By: Relevance
“…Rarely, heroin-induced rhabdomyolysis can be complicated by other consequences of coma and pressure, leading to prolonged and incomplete recovery, as case reports have shown: myelitis, neuropathies and compartment syndromes can complicate the picture." 26 Compartment syndromes are not uncommon. Intracompartmental pressures should be measured when necessary, and fasciotomy may need to be performed.r" Once suspected, the diagnosis of heroin-induced rhabdomyolyosis is usually straightforward.…”
Section: Diamorphine (Heroin)mentioning
confidence: 99%
“…Rarely, heroin-induced rhabdomyolysis can be complicated by other consequences of coma and pressure, leading to prolonged and incomplete recovery, as case reports have shown: myelitis, neuropathies and compartment syndromes can complicate the picture." 26 Compartment syndromes are not uncommon. Intracompartmental pressures should be measured when necessary, and fasciotomy may need to be performed.r" Once suspected, the diagnosis of heroin-induced rhabdomyolyosis is usually straightforward.…”
Section: Diamorphine (Heroin)mentioning
confidence: 99%
“…These findings contrast with those of other authors who have reported renal (O'Brien. Yeoman & Hobby 1971;Taher et al 1974;Bennett & Forman 1980;Fischman & Oster 1979;Moss et al 1980;Kroeger et al 1980;Streicher et al 1981;Will & McLaren 1971) and hepatic (O'Brien, Yeoman & Hobby 1971) toxicity. Many of these patients appear to have abused drugs and alcohol in addition to toluene (Streicher et al 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Many older 'sniffers' (i.e. aged [14][15] years) are also alcoholics as defined by answering 'yes' to 4 or more questions from the Heilman questionnaire.…”
Section: Identification and Evaluationmentioning
confidence: 99%